Collision skin lesions—results of a multicenter study of the International Dermoscopy Society (IDS) - Blum, Andreas; Siggs, Graeme; Marghoob, Ashfaq A.; Kreusch, Jürgen; Cabo, Horacio; Campos-do-Carmo, Gabriella; Cavalcanti Shiraishi, Ana Flávia; Kienitz, Alexander; Maldonado-Seral, Cayetana; Maltagliati-Holzner, Paola; Mijuskovic, Zeljko P.; Yoshimura, Andrea Miyuki; et al. (Dermatology Practical & Conceptual, 2017)
Background: Collision lesions as two independent and unrelated skin tumors often manifest an atypical morphology. Objective: To determine the combinations of collision skin lesions (CSLs).Methods: Twenty-one pigmented lesion clinics in nine countries included 77 histopathologically proven CSLs in this retrospective observational study.Results: Seventy-seven CSLs from 75 patients (median age 59.8 years) were analyzed; 24.7% of CSLs were located on the head and neck area, 5.2% on the upper extremities, 48.1% on the trunk, and 11.7% on the lower extremities; 40.3% revealed a melanocytic component (median age 54.7 years), followed by 45.5% with a basal cell carcinoma (BCC) (median age 62.4 years) and 11.7% with a seborrheic keratosis (median age 64.7 years). CSLs with a BCC component were more often found on the head and neck area compared to tumors with a melanocytic component (34.3% versus 16.1%). Lesions with a melanocytic component were more often detected on the trunk compared to lesions with a BCC (64.5% versus 37.1%). Patients with CSLs with epidermal-epidermal cell combination were older than patients with epidermal-dermal cell combination (63 versus 55.2 years), were more often male than female (63% versus 43.3%), more often had the lesion on the head and neck area (32.6% versus 13.3%), and less often on the upper (2.2 % versus 10%) or lower extremities (8.7% versus 16.6%).Conclusions: CSLs consist of a heterogeneous group of lesions of varying cell types. They are associated with advancing age and cumulative UV-exposure. CSLs manifest a complex morphology making it challenging to diagnose correctly.